An Existence Result for Neutral Delay Integrodifferential Equations with Fractional Order and Nonlocal Conditions - Fang Li; Gaston M. N'Guérékata (Abstract and Applied Analysis, 2011)
We study the existence of mild solutions of a class of neutral delay integrodifferential equations with fractional order and nonlocal conditions in a Banach space X. An existence result on the mild solution is obtained by using the theory of the measures of noncompactness and the theory of condensing maps. Two examples are given to illustrate the existence theorem.